PENDIDIKAN AL ISLAM GUNA MENCEGAH KENAKALAN REMAJA DI DESA ABUNG JAYO - muinah muinah; Sigit Gunanto; Fhella Vhantoria. N (Pengabdian Kepada Masyarakat Cendekia, 2023)
Real Work Lectures (KKN) are a form of community service by holding socialization and mentoring activities with the community as a means of increasing knowledge. Abung Jayo Village is one of the villages selected to implement KKN Transfer Knowledge. Implementation of the Knowledge Transfer KKN program begins with planning, implementation and evaluation at the end of each program. The results achieved from the entire KKN program include Socialization, Visits, Recitations, Tutoring, TPQ Teaching, and Socialization about Juvenile Delinquency.